The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1177/03400352221089675
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of crisis management in libraries with emphasis on crisis preparedness

Abstract: Crisis preparedness is critical for crisis management in all organizations, including libraries. Libraries must make decisions about crisis situations, which requires planning and preparedness for crises. The purpose of this systematic review was to analyse and identify the main issues that assist libraries in decision-making in times of crisis. A total of 2900 studies from 1985 to 2020 were identified. Following the application of inclusion and exclusion criteria, 44 studies were included in the final review … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…Yet, a situation that poses a genuine risk to the lives of every member of the library staff is typically not covered by the ordinary risk management strategy for the institution. ( Akhshik & Beglou, 2023 ) and this study showed that it is time for libraries to change that. While at the beginning of the crisis, the focus was on physical health, then after a while, the mental health of the staff because also a topic to be considered ( LIBER, 2020a , LIBER, 2020b ; Frederick and Wolff-Eisenberg, 2020, April 2 , Frederick and Wolff-Eisenberg, 2020, December 9 ; LIBER, 2020b ; Lembinen, 2022 ).…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…Yet, a situation that poses a genuine risk to the lives of every member of the library staff is typically not covered by the ordinary risk management strategy for the institution. ( Akhshik & Beglou, 2023 ) and this study showed that it is time for libraries to change that. While at the beginning of the crisis, the focus was on physical health, then after a while, the mental health of the staff because also a topic to be considered ( LIBER, 2020a , LIBER, 2020b ; Frederick and Wolff-Eisenberg, 2020, April 2 , Frederick and Wolff-Eisenberg, 2020, December 9 ; LIBER, 2020b ; Lembinen, 2022 ).…”
Section: Discussionmentioning
confidence: 76%
“…The research shows that libraries have disaster plans for potential physical harm to collections (fire, water, or natural disasters like hurricanes) and usually focus on small-scale disasters, but often an action plan in the case of an immediate shutdown is lacking. While the prior research focuses on preparations and response to the crisis in libraries ( Akhshik & Beglou, 2023 ), the focus is not on libraries' leadership.…”
Section: Introductionmentioning
confidence: 99%
“…The second cluster in Figure 1 primarily focuses on organizational requirements, with a strong emphasis on the preand post-disaster processes (Akhshik et al, 2023;Takefuji, 2023). The studies in this cluster concentrate on the impact of disasters on human life, and the pre-disaster actions mainly include public health, education, and preparedness (Sawalha, 2023;Ramasamy et al, 2022;Pastrana-Huguet et al, 2022;Lillywhite et al, 2022).…”
Section: Disaster Managementmentioning
confidence: 99%
“…A systematic review by Akhshik and Beglou (2022) took into account the main strategies used by libraries to prepare for a crisis. Their findings show that preparedness instruction, training programmes, preparation assessment and important crisis management factors were the topics most frequently discussed in libraries with regard to crisis management.…”
Section: Literature Reviewmentioning
confidence: 99%